Dietary glucose oxidase supplementation improves growth performance, intestinal morphology, and microbial community of broilers - Zhu, Xin; Zhang, Xinjie; Zhang, Yong; Zhu, Yujing; Li, Fangfang (Frontiers in Animal Science, 2025)
IntroductionThe objective of this study was to evaluate the influences of dietary glucose oxidase (GOD) supplementation in the growth and slaughter performance, organ index, intestinal morphology and cecal microbiota in broilers.MethodsA total of 480 one-day-old Arbor Acres male broiler chicks were randomly assigned to four groups, and the level of GOD in the diet was 0 (control), 200, 400, and 800 mg/kg. Each group had six replicates and each replicate had 20 chicks. The experimental period was 42 days.ResultsCompared to those in the control, the final body weight (BW) and average daily gain (ADG) were increased (p < 0.05) and the feed conversion ratio (FCR) was decreased (p < 0.05) in the 400 mg/kg and 800 mg/kg GOD groups. Dietary supplementation with 800 mg/kg GOD increased (p < 0.05) the dressing-out percentage; semieviscerated yield; relative weights of the thymus, spleen and bursa of Fabricius; and the lengths and weights of the duodenum, jejunum, ileum, and total small intestine compared to those in the control group. Additionally, dietary supplementation with GOD increased (p < 0.05) the villus height and villus height/crypt depth ratio and decreased (p < 0.05) the crypt depth of the duodenum and ileum compared to those of the control group. Illumina sequencing data indicated that the Simpson index of the cecal microbiota in the GOD group was decreased, indicative of increased microbial diversity. Compared to the control, GOD supplementation increased (p < 0.05) the abundances of the genera Ralstonia, Akkermansia and Parabacteroides.DiscussionTherefore, the results from this study indicated that dietary GOD supplementation could improve the growth performance and carcass yields, promote immune organ and gut development, and enhance the intestinal morphology and cecal microbiota composition in broilers.